State Role In Building Peoples Economy Amid Economic Globalization - Elly Nurlaili (UBL, 2013)
Indonesian nation demanded an active role in building a new world order and a new economic order thatis orderly, fair and prosperous, while continuing to protect national interests and ensure social justice inaccordance with the principles of economic democracy outlined by Article 33 of the 1945 Constitution.Therefore, have to be prepared the legal / justice system that is able to anticipate the development of theinternational political economy, by building the legal system of national economy, which is based on theprinciples of the 1945 Constitution, to achieve the goals it is necessary to do a reorientation of the role ofthe state in economic reform. Economic reforms by build up the people's economy through cooperativeinstitutions, small and medium businesses. Economic development of the people has the twin objectivesof improving the efficiency of the national economy and at the same time removing various economicinjustice with the ultimate goal the establishment of a just and prosperous society based on Pancasila